Shifting of Agriculture to Horticulture in Anantnag District: A Geographical Analysis - Tajamul Hussain Sheikh; Rayees Ahmed; Archana Purohit (International Journal of Agriculture System, 2022)
The vast area of paddy crop in Anantnag district (Jammu and Kashmir) has been converted for the construction of houses, roads and especially for horticultural purposes. The cultivation of paddy has been an old cultural heritage of Anantnag district as well as for the Kashmir valley as a whole, while the farmers are increasingly finding it less profitable in recent times. The present study used both primary (Survey) and secondary data from different sources with an aim to highlight the issue of diversifying of food crops (Paddy) towards cash crops (Apple) in district Anantnag. The findings from the study reveal that 6908 hectares of agricultural cropped area is shifted towards the horticultural cropped area, as agricultural crops (paddy) have low comparative advantage over horticultural (Apple). Paddy land under surveyed farmers has registered a significant decrease from 330 canals (83.75%) in 2000-01 to 158 canals (40.11%) in 2014-15, therefore showing an absolute change of -172 canals. The primary survey further reveals that 09 (30%) of the respondents says less profit is the main reason behind the shift, followed by irrigation (drought) problems 07 (23.34%) and 14 (46.66%) respondents says both reasons are responsible behind shift of Paddy to Apple cultivation in the region.